2022
DOI: 10.3389/fmed.2021.816802
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Pathological Mechanism of Frequent Exacerbators With Chronic Obstructive Pulmonary Disease Based on the Characteristics of Respiratory Flora

Abstract: Chronic obstructive pulmonary disease (COPD) is a common obstructive respiratory disease characterized by persistent respiratory symptoms and limited airflow due to airway obstruction. The present study investigates the distribution characteristics of respiratory tract flora in both frequent and infrequent exacerbators of COPD. The 16S sequencing technique was adopted to differentiate the inherent differences of respiratory tract flora between frequent exacerbators and infrequent exacerbators. Additionally, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…It has been documented that Veillonella parvula can cause spondylitis [1] , osteomyelitis [3] , and epidural abscesses in immunocompromised patients [13] . This bacterium has been seen in children with pneumonia [14] and acromioclavicular septic arthritis [15] , reduces the activity of bronchial epithelia in obstructive pulmonary disease [16,17] and produces nasal sepsis [18] . It has also been found at a high level in patients with COVID 19 [19] , as well as with early childhood caries [20] , lung cancer [21] , nasopharyngeal carcinoma [22] , and epithelial squamous cell carcinoma [23] .…”
Section: Bacteremia Due To Veillonella Parvulamentioning
confidence: 99%
“…It has been documented that Veillonella parvula can cause spondylitis [1] , osteomyelitis [3] , and epidural abscesses in immunocompromised patients [13] . This bacterium has been seen in children with pneumonia [14] and acromioclavicular septic arthritis [15] , reduces the activity of bronchial epithelia in obstructive pulmonary disease [16,17] and produces nasal sepsis [18] . It has also been found at a high level in patients with COVID 19 [19] , as well as with early childhood caries [20] , lung cancer [21] , nasopharyngeal carcinoma [22] , and epithelial squamous cell carcinoma [23] .…”
Section: Bacteremia Due To Veillonella Parvulamentioning
confidence: 99%
“…However, many studies have suggested that elevated abundance of Veillonella can cause a range of diseases. For example, V. parvula has been detected in blood, bone, the oral cavity, urinary tract, heart valves, cerebrospinal fluid, respiratory tract, and gastrointestinal tract, causing multiple diseases including bacteremia, intervertebral discitis, dental caries, urinary tract infection, endocarditis, meningitis, and inflammatory bowel disease (IBD) (Chang et al 2023;Rojas-Tapias et al 2022;Li et al 2017;Bhatti and Frank 2000;Ke et al 2022;Berenger et al 2015;Chen et al 2021;Washio et al 2014). Under normal conditions, Veillonella is not present in the blood, bones, heart valves, or cerebrospinal fluid, and if detected at these sites, it is considered a potential pathogen.…”
Section: Introductionmentioning
confidence: 99%